PROBLEMATIKA HUKUM PERKAWINAN DI INDONESIA - Novita Lestari (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: Indonesia is a very plural country, consisting of various tribes, groups, races and religions and rich in culture. The heterogeneity of Indonesian society makes it possible for marriages of different religions and other forms of marriage. The special law regulating marriage is Law Number 1 Year 1974. Many parties assume that Law Number 1 Year 1974 needs to be revised because the law has been too long and can not solve some problems of marriage in the modern era . Therefore, there are still many rules that need to be changed or added in the Marriage Law, for example about the rules / provisions regarding strict sanctions for marriage offenders, whether for the perpetrators of religious marriages, similar marriages, marriage sirri and contract marriage.